2020
DOI: 10.1097/md.0000000000021458
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid and blood levels of neurofilament light chain in Parkinson disease

Abstract: Background: Parkinson disease (PD) is a common neurodegenerative disorder. Elevations of neurofilament light chain (NfL) concentrations in the cerebrospinal fluid (CSF) and blood are a marker of neuronal/axonal injury and degeneration. However, CSF and blood NfL alterations in patients with PD from existing studies remain inconclusive. To better understand these conflicting data, we will conduct a meta-analysis. Methods: We will comprehensively search PubMed, Embase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(31 reference statements)
0
4
0
Order By: Relevance
“… Temporal course of changes in FRDA. Diagram illustrating the contrasting temporal course of clinical changes in FRDA along with serum NfL levels over time (amalgamated from Bridel et al, 2019 ; Del Prete et al, 2020 ; Wang et al, 2020 ). Clinical changes are presented based on the clinical course of an early onset individual (onset between ages 5−10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Temporal course of changes in FRDA. Diagram illustrating the contrasting temporal course of clinical changes in FRDA along with serum NfL levels over time (amalgamated from Bridel et al, 2019 ; Del Prete et al, 2020 ; Wang et al, 2020 ). Clinical changes are presented based on the clinical course of an early onset individual (onset between ages 5−10).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cardiac troponin levels are elevated in FRDA serum during the period of hypertrophic disease, long before cardiomyocytes die and cardiac fibrosis develops (Friedman et al, 2013;Plehn et al, 2018;Legrand et al, 2020). Such elevated levels Bridel et al, 2019;Del Prete et al, 2020;Wang et al, 2020). Clinical changes are presented based on the clinical course of an early onset individual (onset between ages 5−10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found decreased CSF levels of glutamate and taurine and increased CSF levels of tyrosine; decreased serum/plasma levels of aspartate, serine, tryptophan, and lysine, and increased serum/plasma proline and homocysteine levels (Jiménez-Jiménez et al, 2020 ). Taken together, these markers, and many other proteins such as circulating microRNAs and neurofilament light (He et al, 2018 ; Khalil et al, 2018 ; van den Berg et al, 2020 ; Wang H. et al, 2020 ), have all been reported to be associated with PD. However, Dos Santos et al ( 2018 ) has also proposed that the potential biomarkers lacked robustness and reproducibility in supporting diagnosis in the early clinical stages of PD; therefore, we still need further validation to confirm these findings.…”
Section: Fluid and Tissue Biomarkersmentioning
confidence: 97%